2020
DOI: 10.1111/anu.13113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary vitamin B1on growth performance, blood metabolites, body composition, intestinal enzyme activities and morphometric parameters of juvenile yellow catfish (Pelteobagrus fulvidraco)

Abstract: The effects of vitamin B1 on growth, blood metabolites, body composition, intestinal enzyme activities and morphometric parameters were evaluated by a 63‐day feeding trial in Pelteobagrus fulvidraco fed diets containing vitamin B1 with 4.29, 6.02, 7.86, 11.94 and 19.05 mg/kg, respectively. Results showed that 7.86 mg/kg vitamin B1 resulted in significantly higher weight gain (WG), specific growth rate (SGR) and protein efficiency ratio (PER) (p < .05). Serum triglyceride, cholesterol and whole‐body lipid were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
4
4
0
Order By: Relevance
“…activity of trypsin, chymotrypsin, amylase, and lipase increased signi cantly with the consumption of thiamin-supplemented diets. These results are consistent with ndings reported in Jian carp(Huang et al 2011), golden pompano(Xun et al 2019), and yellow cat sh (Pelteobagrus fulvidraco) juveniles(Zhao et al 2020). In contrast with the present study,Xun et al 2019 reported that dietary thiamin content did not signi cantly affect amylase activity in golden pompano.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…activity of trypsin, chymotrypsin, amylase, and lipase increased signi cantly with the consumption of thiamin-supplemented diets. These results are consistent with ndings reported in Jian carp(Huang et al 2011), golden pompano(Xun et al 2019), and yellow cat sh (Pelteobagrus fulvidraco) juveniles(Zhao et al 2020). In contrast with the present study,Xun et al 2019 reported that dietary thiamin content did not signi cantly affect amylase activity in golden pompano.…”
supporting
confidence: 92%
“…In the present study, TP, TG, and CHO were signi cantly affected by different levels of thiamin. Similar results were reported byZhao et al 2020. The results obtained herein from the evaluation of blood metabolites show that the concentration of thiamin in the diet at 15 and 25 mg/kg feed increases serum TP contents with no signi cant difference between them.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Wheat flour, fish oil and soybean oil were used as carbohydrate and lipid sources. The levels of nutrients met the requirements of yellow catfish according to previous studies conducted in our laboratory ( Cao et al, 2012 ; Chen et al, 2016 ; Zhao et al, 2020 ). Five isonitrogenous and isolipidic diets were formulated to contain SB at 0 (control), 250, 500, 1,000 or 2,000 mg/kg, by supplementing SB (purity ≥ 98%).…”
Section: Methodsmentioning
confidence: 94%